Naravovarstvena problematika sten and Ospom kot gnezdišča velike uharice Bubo bubo - Mihelič, Tomaž (Acrocephalus, 2000)
Eagle Owl Bubo bubo retreats from rock walls as soon as entered by climbers. In the present article the authors attempt to establish a link between the retreat by the breeding Eagle Owl and the people climbing in the rock walls ofOsp and Mišja peč at Kraški rob (Karst edge). Climbers frequent these walls particularly in January and April when this owl is certainly most sensitive. In the walls of Osp, regular climbing began in 1980. Three years later the Eagle Owl moved to the neighbouring Mišja peč, but as climbing began to be practised here in 1986 as well, the owl moved during the following year to a less suitable nest-site nearby. The authors found a clear link between the climbers' activities in rock walls and the breeding Eagle Owl's retreat to substitutional nest-sites.
Keywords: bird; Birds; ptice; Ecosystem; ornitologija; gnezdenje; Nesting behavior; Sports; varstvo narave; environmental protection